Exploring Mo-ZnO@NF for hydrogen generation and methylene blue remediation: sunlight-driven catalysis - Padwal, Yogita; Chauhan, Ratna; Panchang, Rajani; Fouad, Hassan; Gosavi, Suresh W. (Frontiers in Physics, 2024)
In this study, we elucidate the synthesis and characterization of molybdenum (Mo) doped zinc oxide (ZnO) nanoflowers (Mo-ZnO@NF) fabricated via a hydrothermal approach, showcasing their potential application in hydrogen generation and dye degradation. The successful synthesis of these nanoflowers is achieved through the deliberate incorporation of Mo ions into the ZnO lattice, yielding a distinctive hierarchical flower-like morphology. Comprehensive structural, morphological, and optical analyses are conducted employing a suite of analytical techniques, encompassing XRD, Raman, FESEM, and UV-Visible spectroscopy. XRD analysis confirms the retention of the hexagonal wurtzite crystal structure, accompanied by discernible peak shifts indicative of Mo ion integration. FESEM imaging further elucidates the flower-like architecture of Mo-ZnO, underscoring the intricate morphological features. Photocatalytic assessment reveals the remarkable efficacy of Mo-ZnO@NF, as evidenced by an unprecedented hydrogen evolution rate of 2024 mmol/h/g and 97% Methylene Blue (MB) dye degradation within a mere 40-minute timeframe. Furthermore, a comparative investigation between pristine ZnO and varying Mo doping concentrations (ranging from 1% to 5%) underscores the optimal doping concentration of 1% Mo in ZnO. This concentration threshold is shown to engender superior photocatalytic performance, potentially attributed to enhanced charge carrier separation and increased surface area conducive to catalytic reactions. Overall, this study not only advances our understanding of Mo-ZnO@NF nanostructures but also elucidates key insights into optimizing their photocatalytic efficacy for diverse environmental remediation applications.